2018
DOI: 10.3389/fmars.2018.00220
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Habitat Use of a Cryptic Small Cetacean, the Burmeister's Porpoise, Monitored From a Small-Scale Fishery Platform

Abstract: There is widespread evidence that small-scale fisheries (SSF) bycatch threatens many populations of small cetaceans, yet conservation efforts are often limited by a lack of basic knowledge regarding their abundance, distribution, and habitat use. Here, we used passive acoustic monitoring from an SSF platform-of-opportunity to better characterize the distribution and habitat use of small cetaceans in northern Peru, focussing on the little-known Burmeister's porpoise Phocoena spinipinnis. From 2009 to 2012, acou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 63 publications
1
14
0
2
Order By: Relevance
“…No difference in elevation/depression angle was observed between the BB and NB periods, suggesting that porpoises did not become entangled because they had dived deeper than in usual. These observations indicate that harbour porpoises risk entanglement by appearing around a bottom-gillnet, and the risk of bycatch increases with repeated appearances, which is similar to the recent report on Peruvian drift net fishery [46].…”
Section: Plos Onesupporting
confidence: 89%
“…No difference in elevation/depression angle was observed between the BB and NB periods, suggesting that porpoises did not become entangled because they had dived deeper than in usual. These observations indicate that harbour porpoises risk entanglement by appearing around a bottom-gillnet, and the risk of bycatch increases with repeated appearances, which is similar to the recent report on Peruvian drift net fishery [46].…”
Section: Plos Onesupporting
confidence: 89%
“…If the animal was alive at sea within the Falklands Exclusive Economic Zone (EEZ) prior to the stranding, explanatory possibilities include: (1) the occurrence was an atypical event outside of the species usual distribution range; (2) individuals occasionally enter the Falklands EEZ during longer-range movements from the South American mainland; or (3) Burmeister's porpoises routinely occur in Falklands' waters but have simply remained unrecorded to date. Recent acoustic deployments detected Burmeister's porpoises in neritic habitat up to 200 m depth and over 100 km offshore in Peru (Clay et al 2018). The wide expanse of Patagonian Shelf located between the Falklands and mainland South America is shallow (< 200 m depth) and potentially also provides suitable neritic habitat for the species.…”
Section: Discussionmentioning
confidence: 99%
“…Corcuera et al 1995;Goodall et al 1995a). They have primarily been reported from nearshore, shallow habitats, including bays, estuaries, channels and fjords (Brownell Jr. and Praderi 1982;Corcuera et al 1994;Goodall et al 1995aGoodall et al , 1995bBrownell Jr. and Clapham 1999), and acoustic data suggest that they preferentially forage in water depths shallower than 50 m and within 30 km of the coast (Clay et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Pingers have had promising results in deterring several species of cetaceans (e.g. Burmeister's porpoises Phocoena spinipinnis) from small-scale driftnets (Clay et al 2018) but have also been shown to attract some pinnipeds ('dinner bell' effect;Carretta & Barlow 2011). Recently, light-emitting diodes reduced gillnet bycatch of small cetaceans in Peru by 70% (Bielli et al 2020).…”
Section: Bycatch Mitigationmentioning
confidence: 99%